Neoliberal rationality in the public procurement to combat the syndemic of Covid-19 - Rufino Filho, Ednaldo Tavares; Vettorato, Poala (Plural, 2022)
The health crisis resulting from COVID-19 constitutes a syndemic, due to the interaction of biological aspects with precarious social conditions. We analyze public acquisitions related to the confrontation of the syndemic, contemplating the Rio Grande do Sul State, and the city of Porto Alegre. This is an exploratory and qualitative study, andthe analysis is carried out after a bibliographic survey on necropolitics and neoliberalism. Data collection was carried out at the management panel of hiring related to Covid-19 of the Comptroller General of the Union. It is observed that the largest bid of the StateBidding Center was computer equipment and, in the municipality, basic basket. When analyzing the government purchases of the municipal and state, it was found that they are permeated by neoliberal rationality.